2018
DOI: 10.1021/acssuschemeng.7b04643
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of d-Fructose to 5-(Hydroxymethyl)furfural: Evaluating Batch and Continuous Flow Conditions by Design of Experiments and In-Line FTIR Monitoring

Abstract: The dehydration reaction of d-(−)-fructose into 5-(hydroxymethyl)­furfural (HMF) in both batch and continuous flow conditions was comprehensively studied using the statistical tool design of experiments (DoE), employing i-PrOH/DMSO as the solvent system in the presence of the solid acid catalyst Amberlyst-15. Initially, screening of different alcohols (MeOH, EtOH, i-PrOH, and t-BuOH) showed that i-PrOH provides better selectivity and yield compared to the other alcohols, along with minimum formation of byprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…Several researches focused on the heterogeneously catalyzed dehydration of fructose to HMF (derivatives) in single phase operation (Table 4, entries [12][13][14], [227][228][229] or xylose to furfural in biphasic flow (Table 4, entries [15][16] [230,231] using milli-scale packed bed reactors (d C = 4-10 mm). These millireactors could be easily transferred into microreactor configurations and thus give valuable insights in the potential of the latter for the heterogeneous synthesis of furans from sugars.…”
Section: Heterogeneously Catalyzed Furan Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Several researches focused on the heterogeneously catalyzed dehydration of fructose to HMF (derivatives) in single phase operation (Table 4, entries [12][13][14], [227][228][229] or xylose to furfural in biphasic flow (Table 4, entries [15][16] [230,231] using milli-scale packed bed reactors (d C = 4-10 mm). These millireactors could be easily transferred into microreactor configurations and thus give valuable insights in the potential of the latter for the heterogeneous synthesis of furans from sugars.…”
Section: Heterogeneously Catalyzed Furan Synthesismentioning
confidence: 99%
“…H 3 BO 3 (combined with NaCl) is an alternative homogeneous catalyst for the synthesis of HMF. [227,228] Above that, HMF ethers have a better storage stability than HMF, which can be advantageous as compared to using HMF as a substrate in the industrial production towards HMF derivatives (e. g., FDCA). However, relatively low reaction rates (40-50 % HMF yield in 45 min at 150°C) were obtained with this catalyst in biphasic batch reactors.…”
Section: Opportunitiesmentioning
confidence: 99%
“…For instance, Galaverna et al. reported that Amberlyst‐15 was a highly efficient catalyst for fructose conversion to HMF in continuous flow conditions with a yield of 95.00 % . Our previous studies have reported sulfonated hierarchical porous carbons and SBA‐15 supported niobium phosphate (Nb−P/SBA‐15) are also very effective for converting fructose to HMF, with HMF yields more than 92.00 % .…”
Section: Introductionmentioning
confidence: 99%
“…Galaverna et al . synthesized HMF from fructose in both batch and continuous flow conditions by employing i ‐PrOH/DMSO as solvent system in the presence of Amberlyst‐15 . And HMF was effectively produced from fructose and glucose using phosphate buffer saline (reaction phase)/2‐ sec ‐butyl phenol (extraction phase) biphasic reaction system in a microreactor by Muranaka and co‐workers .…”
Section: Introductionmentioning
confidence: 99%
“…[8] Galaverna et al synthesized HMF from fructose in both batch and continuous flow conditions by employing i-PrOH/DMSO as solvent system in the presence of Amberlyst-15. [9] And HMF was effectively produced from fructose and glucose using phosphate buffer saline (reaction phase)/2-sec-butyl phenol (extraction phase) biphasic reaction system in a microreactor by Muranaka and co-workers. [10] Moreover, acidic metal phosphates were shown to be effective for conversion of monosaccharides into HMF, due to its acidity, structure superiorities with large surface areas and large pores, high thermal stability, allowing its possible recovery and reuse in recent years.…”
Section: Introductionmentioning
confidence: 99%